Piezoelectric energy harvesting for naval ship applications - Wang, Jichen (2014)
Ambient vibration energy Harvesting has been considered to be a useful method to supply power to wireless sensors and this technology can be incorporated in naval ships for powering various sensors. In order to perform sensing functions while having maintenance free specified service time interval, the harvesters have to be designed to generate sufficient power to supply for more variety of sensors and devices while able to last for long duration. In this report, selection of ideal substrate material has been done and optimal configurations of harvesters have been tested. Linear and non-linear piezoelectric energy harvester experimental tests have also been carried out to study the power output response for the three types of substrate materials. Experimental and simulation analysis results have proven that the Aluminium 7075 is the most ideal substrate to be used in piezoelectric energy harvesting applications. The proposed linear PEH assumptions are valid for the most of the energy harvesting applications including for the vibrations in naval ships.